Peluang dan Tantangan Ekspor Indonesia ke China di Tengah Dinamika Tarif Perdagangan Global - Nur Halimah (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
The product coated, covered or laminated textile fabrics (HS Code 59) is a high value-added technical textile commodity with significant potential to be developed as Indonesia's flagship export to the Chinese market. China is recognized as one of the world's largest textile importers, making it both a strategic and competitive destination for Indonesian textile products. This study aims to analyze the opportunities and challenges facing Indonesia in exporting this commodity to China amid evolving global trade tariff dynamics. The method employed is a descriptive analysis using quantitative and qualitative approaches based on data from Statistics Indonesia (BPS) and the ASEAN-China Free Trade Agreement (ACFTA) framework. The findings indicate that export opportunities are available through ACFTA preferential tariffs, growing Chinese demand for quality technical textiles, and shifts in global supply chains driven by the escalating US-China trade war. Key challenges include a consistent decline in export value, intense competition from other producing nations, complex Chinese quality regulations, and domestic limitations in technology and production capacity. Enhancing competitiveness through technology modernization and optimal utilization of preferential tariff schemes is essential for driving sustainable export growth of this commodity.